2014
DOI: 10.18044/medinform.201411.35
|View full text |Cite
|
Sign up to set email alerts
|

Could Inosine pranobex and Ribavirin in combination restore immune competence in chronic HCV advanced liver disease?

Abstract: The management of patients with advanced chronic HCV liver disease is still a problem. There is insufficient data about the role of immunomodulatory agents. The aim of the present study was to evaluate the benefit of prolonged co-administration of Inosine pranobex (Isoprinosine) and Ribavirin in patients with HCV advanced liver disease and to assess the dynamics of the IP-10 serum levels and thus -changes in the immune status of patients. Methods: Five patients (2 males, 3 females; median age 63), with chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our findings of survival or protection could be explained on the basis of the significant decrements of NDV titer in IAD only, Vaccine only and IAD + Vaccine groups comparing with control group indicated by PCR. Despite absence of similar findings in chickens, yet decreasing other virus titers by Isoprinosine may be supportive findings of the present study; for instance, [15] and [16] found that treatment with Isoprinosine decreased HB and HC virus titers, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings of survival or protection could be explained on the basis of the significant decrements of NDV titer in IAD only, Vaccine only and IAD + Vaccine groups comparing with control group indicated by PCR. Despite absence of similar findings in chickens, yet decreasing other virus titers by Isoprinosine may be supportive findings of the present study; for instance, [15] and [16] found that treatment with Isoprinosine decreased HB and HC virus titers, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Immunomodulation therapy for patients with hepatitis C virus infection has been addressed only in individual cases or small groups of people [84, 85]. Use of IP, as monotherapy or in combination with ribavirin, had no impact on viral load.…”
Section: Therapeutic Trialsmentioning
confidence: 99%
“…However, normalization of alanine aminotransferase levels was observed in patients non-responsive to IFN treatment [85]. In addition, concomitant use of IP with ribavirin improved disease severity and liver inflammation, evidenced by a reduction in the levels of the IFN-γ-inducible protein 10 [84]. If similar results are obtained in the future in controlled studies with larger numbers of patients, the beneficial role of IP, especially in the case of patients non-responsive to mainstay treatments, could be established.…”
Section: Therapeutic Trialsmentioning
confidence: 99%
“…Antiviral and immunomodulating activities of Isoprinosine were recently demonstrated in children with cellular immunodeficiency as a prophylaxis of recurrent viral infections (3). Previous studies discussed also its possible role in the treatment of chronic hepatitis B and C (1,(4)(5)(6), including the prevention of hepatic flare after discontinuation of lamivudine (7). (8).…”
Section: Introductionmentioning
confidence: 99%